The Place of the marine environmental security in the concept of ensuring of environmental security for South-east Asian states - Ngoc Anh Nguyen (RUDN Journal of Law, 2012)
The article analyzes the international legal cooperation of South-east Asian states in insuring marine environmental security. It contains a brief analysis of the most important universal treaties on this subject and of the membership of states of the region in them. The author considers participation of South-east Asian states’ in the program for protection and sustainable development of marine and coastal environment in the framework of such regional structures as the Association of South-east Asian Nations (ASEAN), Regional Seas Program for East Asia (COBSEA) and Asia-Pacific Economic Cooperation (APEC). It is concluded that the problem of marine environmental security should hold a principally important place in the concept of environmental security of states of the region. For this purpose they need to strengthen institutional and legal mechanism for marine environmental security at both global and regional level.